2023
DOI: 10.3390/ijms241914856
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Responses of Tibetan Sheep Rumen Microbiota, Metabolites, and the Host to the Plateau Environment

Yuzhu Sha,
Xinyu Guo,
Yanyu He
et al.

Abstract: Plateau adaptation in animals involves genetic mechanisms as well as coevolutionary mechanisms of the microbiota and metabolome of the animal. Therefore, the characteristics of the rumen microbiome and metabolome, transcriptome, and serum metabolome of Tibetan sheep at different altitudes (4500 m, 3500 m, and 2500 m) were analyzed. The results showed that the rumen differential metabolites at 3500 m and 4500 m were mainly enriched in amino acid metabolism, lipid metabolism, and carbohydrate metabolism, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…These differentially abundant metabolites were enriched mainly for functions related to amino acid synthesis and metabolism and lipid metabolism, suggesting that Astragalus root powder can promote metabolism, immunity, antioxidant activity, and other functions. In addition, the present study revealed that upregulated metabolites were enriched in the metabolism of xenobiotics by cytochrome P450 and involved bile secretion in the regulation of the immune pathway [ 48 ], and bile has been reported to protect organisms from intestinal infections through the secretion of immunoglobulin A (IgA) and inflammatory cytokines and the stimulation of the intrinsic immune system of the intestinal tract [ 49 ]. Therefore, Astragalus root powder can promote bile secretion and enhance the function of the rumen epithelial immune barrier in lambs.…”
Section: Discussionmentioning
confidence: 99%
“…These differentially abundant metabolites were enriched mainly for functions related to amino acid synthesis and metabolism and lipid metabolism, suggesting that Astragalus root powder can promote metabolism, immunity, antioxidant activity, and other functions. In addition, the present study revealed that upregulated metabolites were enriched in the metabolism of xenobiotics by cytochrome P450 and involved bile secretion in the regulation of the immune pathway [ 48 ], and bile has been reported to protect organisms from intestinal infections through the secretion of immunoglobulin A (IgA) and inflammatory cytokines and the stimulation of the intrinsic immune system of the intestinal tract [ 49 ]. Therefore, Astragalus root powder can promote bile secretion and enhance the function of the rumen epithelial immune barrier in lambs.…”
Section: Discussionmentioning
confidence: 99%